2017 IEEE International Geoscience and Remote Sensing Symposium (IGARSS) 2017
DOI: 10.1109/igarss.2017.8127282
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Azimuth Display simulator for wind-Doppler lidar error assessment

Abstract: UPCommonsPortal del coneixement obert de la UPC http://upcommons.upc.edu/e-prints

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In previous works [40], we have presented the formulation of the VAD motion simulator under the assumption of a time-invariant and horizontally-homogeneous wind field. The simulator uses Euler's angles to compute the rotated line-of-sight vector at a given time in response to simultaneous pitch, roll, and yaw tilting angles (three degrees of freedom).…”
Section: The Velocity-azimuth-display Motion Simulatormentioning
confidence: 99%
See 4 more Smart Citations
“…In previous works [40], we have presented the formulation of the VAD motion simulator under the assumption of a time-invariant and horizontally-homogeneous wind field. The simulator uses Euler's angles to compute the rotated line-of-sight vector at a given time in response to simultaneous pitch, roll, and yaw tilting angles (three degrees of freedom).…”
Section: The Velocity-azimuth-display Motion Simulatormentioning
confidence: 99%
“…In previous works [40] limited to one degree of freedom in angular motion (i.e., roll or pitch only), the authors have shown that wind direction has a relevant impact on the HWS error. In addition, under one-degree-of-freedom harmonic motion, it has been shown that the HWS error exhibits sinusoidal dependence with wind direction.…”
Section: Wind Direction Exclusionmentioning
confidence: 99%
See 3 more Smart Citations